Potential of Endophytic Bacteria from Rambusa Plant as Disease Control and Growth Promoters of Samarinda White Pepper (Piper nigrum L.) - Hidayat, Nur; Mudi, La; Alkas, Taufiq Rinda; Faradilla, Faradilla; Mentari, F. Silvi Dwi; Daryono, Daryono; Adipratama, Ryan; Wandy, Syahrul (Journal of Applied Agricultural Science and Technology, 2024)
Stem base rot (SBR) disease caused by Phytophthora capsici Leonian is associated with significant yield loss. Meanwhile, wild passion fruit (Passiflora foetida L.) interacts with bacteria that have potential to control SBR disease. Therefore, this research aimed to examine potential of endophytic bacteria from wild passion fruit to control SBR disease in pepper plant and the role as growth promoters. A total of 12 endophytic bacteria isolates were tested for potential to promote growth and biocontrol, focusing on the ability to produce the phytohormone IAA, dissolve phosphate, fix nitrogen, as well as produce cellulase and protease enzymes. The three best isolates were then tested on pepper cuttings (Var. Malonan I). The results showed that the highest disease severity was found in control at 40.74% (moderately susceptible), followed by isolate KSA 01 at 37.03%, and SIB 01 at 33.33% (resistant). Disease severity in isolate KPA 03 was significantly lower at 7.41% (very resistant). The highest disease incidence occurred in control and KSA 03 at 44.44%, while the lowest occurred in KPA 03 and SIB 02 at 33.33%. Isolate KPA 03 produced the highest plant height increase (39.87 cm) and the highest number of leaves (5.78), although it was not significantly different from isolate SIB 02. This research showed that endophytic bacteria from wild passion fruit could effectively control SBR disease and improve pepper plant growth.